Analisis perkembangan sikap sosial peserta didik kelas iv sd dalam materi keragaman suku di Indonesia - Nisa Nurbaiti; Siti Istiyati; Hadiyah Hadiyah (Universitas Sebelas Maret, 2022)
Abstract. Many of tribe in Indonesia is one of trouble by student in developing social attitude. As is the development of modern times have been difficult to make students much. This is for the writers to develop social attitudes in the diversity of students in indonesia. Research aims to understand how to develop social attitudes students in matter of diversity in indonesia. Methods used in this research is qualitative research descriptive by approach case study. A subject of study taken was the teacher and students kaliwatu the fourth grade. Data collection techniques used the interview techniques, the survey, observation, and documentation. The research data conducted by researchers that social attitudes fourth grade students the kaliwatu has grown well. This is proven by the data collection taken by researchers. Social attitudes can develop if implanted habituation fairly well through. Social attitudes and social behavior shown by teachers, parents, peers, and the public may see and tirukan students. For that reason, students have to show develops attitudes and social well.Keywords: development social attitude, student, diversity of tribe